2021
DOI: 10.1111/hel.12836
|View full text |Cite
|
Sign up to set email alerts
|

Association between bacteria other than Helicobacter pylori and the risk of gastric cancer

Abstract: Background The gastric microbiota, including Helicobacter pylori (HP), has a remarkable role in gastric cancer (GC) occurrence. Evidence for the role of non‐HP bacteria in GC risk is limited. We aimed to observe the association between bacteria other than HP and risk of GC in a Korean population. Methods In this study, 268 GC cases and 288 healthy controls were included. Demographic data and total energy intake data were collected using a general questionnaire and a semiquantitative food frequency questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
(90 reference statements)
0
17
0
Order By: Relevance
“…Gastric carcinogenesis is canonically described as a multi-step process driven by numerous etiological factors ( 43 , 44 ). Among these, cadherin 1 mutations cause diffuse types of GC with a poor clinical prognosis in the early stages of life ( 7 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gastric carcinogenesis is canonically described as a multi-step process driven by numerous etiological factors ( 43 , 44 ). Among these, cadherin 1 mutations cause diffuse types of GC with a poor clinical prognosis in the early stages of life ( 7 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gunathilake et al analyzed 268 GC cases and 288 healthy controls and found significant differences in the composition of the non-HP microbiota among the groups. Participants with higher relative abundance of Actinobacteria species showed a markedly increased risk of GC (67). Differences existed between GC patients and healthy controls not only in the TM, but also in the serum microbiome.…”
Section: Gastric Cancermentioning
confidence: 93%
“…Metagenomic analysis of bacteria and extracellular vesicles conducted by Choi et al the following year found that Helicobacter pylori and Streptococcus were two major bacterial genera, and their abundances increased significantly in gastric cancer patients (Choi et al, 2017). In 2020, Gunathilake et (Gunathilake et al, 2021). The above studies showed that the abundance of Streptococcus was significantly increased in gastric cancer at the genus level, but at the species level, the abundances of some Streptococcus species were decreased in gastric cancer.…”
Section: Changes In Endogastric Streptococcus During the Occurrence A...mentioning
confidence: 98%